INSTITUTIONAL EXPERIENCE WITH LAPAROSCOPIC ANTERIOR VAGINOCERVICOPEXY USING A MESH IMPLANT IN PATIENTS WITH ANTERIOR COMPARTMENT DEFECT AND APICAL PROLAPSE OF VARYING SEVERITY - Chekhanov, Yurii O.; Chekhanov , Oleksandr Yu.; Gladchuk, Igor Z. (Eastern Ukrainian Medical Journal, 2026)
Introduction. In reconstructive pelvic floor surgery using synthetic implants, several laparoscopic techniques have evolved as alternatives to sacrocolpopexy. Laparoscopic vaginocervicopexy is intended to correct apical descent together with anterior compartment failure. Since its first publication, the technique has been repeatedly modified, emphasizing the need to evaluate outcomes of different technical refinements across clinical scenarios. The aim of this study was to report a single-center experience with a modified laparoscopic vaginocervicopexy technique and to assess its effectiveness in relation to defect location and severity.Methods. Outcomes of 137 women with apical and combined prolapse (apical defect with cystocele), including women with a preserved uterus and women after hysterectomy, operated on in 2018–2024 were analyzed. The modification included intraoperative individualization of mesh dimensions based on measured dissection length and width, followed by bilateral fixation to the aponeurosis of the anterior abdominal wall. The assessment included intraoperative and postoperative complications, recurrences, repeat surgeries, operative time, length of hospital stay, and patient-reported satisfaction measured with a standardized satisfaction questionnaire using a five-point response scale. Mean follow-up was 12.8 months.Results. Mean age at surgery was 61.56 ± 9.59 years. The complication rate was 1.46 %, and the recurrence rate was 3.65 %. Mean operative time was 90.36 ± 14.33 minutes, and mean hospitalization duration was 52.20 ± 6.27 hours. Intraoperative blood loss did not exceed 150 mL. Patient-reported satisfaction was high, with a mean score of 4.54 ± 0.41 points, without meaningful differences across clinical groups.Discussion. The modified laparoscopic vaginocervicopexy with individualized mesh sizing and bilateral fixation to the anterior abdominal wall aponeurosis demonstrated favorable mid-term outcomes, combining high effectiveness with low complication and recurrence rates in women with apical prolapse and cystocele.